2023
DOI: 10.1097/mnm.0000000000001667
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning approach using 18F-FDG PET-based radiomics in differentiation of lung adenocarcinoma with bronchoalveolar distribution and infection

Abstract: Objective In this study, we aimed to evaluate the role of 18F-fluorodeoxyglucose PET/computerized tomography (18F-FDG PET/CT)-based radiomic features in the differentiation of infection and malignancy in consolidating pulmonary lesions and to develop a prediction model based on radiomic features. Material and methods The images of 106 patients who underwent 18F-FDG PET/CT of consolidated lesions observed in the lung between January 2015 and July 2020 were evaluated using LIFEx software. The region of interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…Results showed that the ML model with the gradient boosting decision tree algorithm with PET-radiomics had the highest classification accuracy, with an AUC of 0.983. Some studies have found similar results [ 16 19 ] (Table 1 ). Thus, 18 F-FDG PET/CT radiomics-based ML analysis can have a great potential in characterizing SPNs.…”
Section: Clinical Application Of 18 F-fdg Pet/ct R...supporting
confidence: 64%
“…Results showed that the ML model with the gradient boosting decision tree algorithm with PET-radiomics had the highest classification accuracy, with an AUC of 0.983. Some studies have found similar results [ 16 19 ] (Table 1 ). Thus, 18 F-FDG PET/CT radiomics-based ML analysis can have a great potential in characterizing SPNs.…”
Section: Clinical Application Of 18 F-fdg Pet/ct R...supporting
confidence: 64%